(untitled) (Journal on studies and research of academic knowledge, 2021)
The Covid-19 pandemic influenced educational systems worldwide, mainly at levels such as elementary school (primary) and middle school (secondary). The Social Isolation Measures decreed at the beginning of the year 2020, resulting in the suspension of face-to-face classes, affected a large part of the world population including children and adolescents to be unable to regularly attend their entire school year and, therefore, exercise their right to education. This article, which is part of a doctoral thesis research project, has as its general objective to propose recommendations, from the legal sciences, that allow to avoid the increase of factors of vulnerability to the educational rights of children and adolescents. In turn, this article focuses on one of the specific objectives of the doctoral thesis: the identification of the main factors that violate the right to education in childhood and adolescence. It starts from an exegetical methodology, for which a deep normative, bibliographic and documentary review is raised to fit, highlighting a first phase of the work in an analytical work, the result of a careful reading of each selected document. Among the main findings, it is mentioned that there is a consensus, among the main international organizations, that the digital divide in Latin America is an element of vulnerability to the right to education of children and adolescents.